Exploring the high-voltage Mg2+/Na+ co-intercalation reaction of Na3VCr(PO4)3 in Mg-ion batteries. Issue 30 (16th July 2019) - Rubio, Saúl; Liu, Rui; Liu, Xiangsi; Lavela, Pedro; Tirado, José L.; Li, Qi; Liang, Ziteng; Ortiz, Gregorio F.; Yang, Yong
Abstract : A Na3 VCr(PO4 )3 cathode facilitates a high voltage Mg 2+ /Na + co-intercalation reaction entailing V 3+ /V 4+ and V 4+ /V 5+ redox couples at 1.7–2.3 V vs. Mg 2+ /Mg. Abstract : Na3 VCr(PO4 )3 has attracted great attention due to its high energy density and stable structure. The substitution of vanadium with chromium led to an increase in the redox potential from 3.4 to 4.2 V ( vs. Na + /Na). In this work, the electrochemical performance of Na3 VCr(PO4 )3 (NVCP) in Mg cells is successfully investigated. Reversible multielectron Mg 2+ /Na + extraction/insertion is observed. Upon charging, NVCP exhibits two plateaus at 1.75 V and 2.3 V vs. Mg 2+ /Mg 0 achieving a maximum reversible capacity of 85 mA h g −1 (a 1.45 electron reaction) enabling oxidation to V V as determined by 51 V NMR and XPS, and accompanied by extraction of sodium from Na2 sites according to 23 Na NMR. During the subsequent cycles Mg 2+ /Na + ions react at 2.3 and 1.7 V, and an additional peak of Mg 2+ at 1.2 V is observed. Alternatively, electrochemical cells were also assembled with activated carbon in a 0.1 M Mg(TFSI)2 electrolyte, leading to similar profiles and capacity even at higher current density. Finally, the chemical desodiation of NVCP using I2, Cl2 and NO2 BF4 is performed to avoid mobile sodium ions. XRD, XPS and 51 V NMR confirmed the contraction of the cell and the oxidation to V IV and V V . Iodine was not capable of full sodium extraction. Despite this fact, the ability of this sample to retain 65 mA h g −1 during a few cycles evidences the reversibility of magnesium insertion. The use of stronger oxidants such as Cl2 or NO2 BF4 allowed the increase of the initial OCV and resulted in a plateau at 4 V. The chemical desodiation was also accompanied by an enhanced capacity decrease which could be correlated with the structural degradation.